Supply Chain 4.0: Autonomous Vehicles and Equipment to Meet Demand - JÃ©ssica Bruna Perussi; Fernando Gressler; Robson Seleme (International Journal of Supply Chain Management, 2019)
The term Supply chain 4.0 refers to the application of industry 4.0 technologies to the supply chain, aiming to plan with greater efficiency and better to meet the demand. Considering this reality, the study aims to verify which equipment and vehicles are being applied and which one presents the best benefits to each stage of the supply chain demand. To define the vehicles and equipment to be analyzed, were presented a supply chain process model, divided among industry, warehouses and customer. Thus, each ones were characterized and the best equipment could be adopted more precisely. The vehicles and equipment were analyzed, considering as the main aspects the maintenance cost, security, operation, product handling, delivery time and sustainability. The results show that the main vehicles to be applied are automated guided vehicles, autonomous trains and drones, each one being applied in different processes of the supply chain.